THE ROLE OF EUPHEMISMS IN POLITICAL SPEECH: A COGNITIVE AND RHETORICAL ANALYSIS - Sharofutdinov, Nodirkhon (QO‘QON UNIVERSITETI XABARNOMASI, 2024)
This paper explores the function of euphemisms in political speech, investigating their role in shaping public perception, mediating controversial topics, and maintaining political stability. Euphemisms are often employed as linguistic strategies to soften the impact of potentially harmful or contentious issues, making them more palatable for the public. Using a combination of cognitive linguistics, discourse analysis, and political rhetoric theory, this study identifies how euphemisms are used to influence political discourse, facilitate communication in delicate matters, and maintain ideological coherence. Through an examination of political speeches, media narratives, and public statements, the paper highlights the complexities of euphemisms as tools of power and persuasion. The analysis also addresses the ethical implications of euphemistic language in politics, noting the potential for manipulation and obfuscation. Ultimately, this research sheds light on how euphemisms shape political communication and public engagement with political issues.